Assessment of Metarhizium anisopliae (Clavicipitaceae) and its vector, Scleroderma guani (Hymenoptera: Bethylidae), for the control of Monochamus alternatus (Coleoptera: Cerambycidae). Issue 5 (22nd December 2014) - Xu, M.; Xu, F.Y.; Liu, Y.P.; Pan, Y.S.; Wu, X.Q.
Abstract: The pinewood nematode, Bursaphelenchus xylophilus (Steiner and Buhrer) Nickle (Aphelenchida: Parasitaphelenchidae), is a major disease of pines forests in China. Its vector, Monochamus alternatus Hope (Coleoptera: Cerambycidae), has been the focus of an intensive study to improve the efficiency of the parasitoid Scleroderma guani Xiao and Wu (Hymenoptera: Bethylidae) by using the parasitoid both as a larval parasitoid in its own right and additionally as a vector for the entomophagous pathogen Metarhizium anisopliae (Metchnikoff) Sorokin (Clavicipitaceae). Twenty-one M. anisopliae strains were screened and the best four tested for sporulation capabilities at a range of temperatures. The best strain was then evaluated at several sporulation concentrations to define the lethal concentration 50 (LC50 ) against the larvae of M. alternatus. Scleroderma guani was inoculated with the best strain and tested against larvae of M. alternatus, which were constrained singly in glass vials. Three S. guani females per vial infected with M. anisopliae (strain 789) were shown to cause the death of 100% of the M. alternatus larvae they were exposed to as compared exposures to just one or two infected S. guani females per vial. This demonstrates a successful interaction of two biocontrol agents for the control of the pinewood nematode vector M. alternatus .